Barriers and facilitators to COVID-19 screening at Jaipur International Airport, India - Neha Mantri; Nitin Kumar Joshi; Pankaj Bhardwaj; Akhil Dhanesh Goel; Manoj Kumar Gupta; Kuldeep Singh; Sanjeev Misra (Journal of Family Medicine and Primary Care, 2022)
Background: Airports pose a possible threat in facilitating global disease transmission within the community which may be prevented by rigorous systematic entry-exit screening. This study captures the perception of stakeholders on barriers and facilitators of coronavirus disease 2019 (COVID-19) screening. Further, key outcomes viz. total passengers screened, suspected cases, and confirmed cases were assessed. Methods: An inductive-deductive mix-method thematic analysis was conducted to capture qualitative data of key stakeholders on COVID-19 disease screening at Jaipur International Airport. Additionally, secondary data retrieved from Rajasthan Medical & Health Department team deployed for COVID-19 airport screening were analyzed. Results: Jaipur International Airport screened 4565 passengers (Males = 4073 and Females = 492) with 23 suspected cases during an outlined period of declaration of Pandemic to Lockdown in India (11 to 24 March 2020). Total 65 passengers had travel history from China (3 from Wuhan). The mean average age of passengers was 40.95 ± 7.8 years. The average screening time per passenger was 2-3 min with a load of 25-90 passengers per team per flight. Fishbone analysis of screening challenges revealed poor cooperation of passengers, masking symptoms, apprehension, and stigma related to quarantine. Moreover, inadequate human resources and changing guidelines overburdened healthcare providers. But, perception of risk, and social responsibility of travelers together with supportive organization behavior act as facilitators. Overall, groundwork on airport screening was insightful to propose key action areas for screening. Conclusions: Globally, COVID-19 has an impact on health infrastructure and international travel. International coordination with streamlined screening will go an extended way in virus containment.